Maternal Health Status in Dikwa Local Government Area of Borno State, Nigeria - Ojemeiri Karl Airaoje; Atinuke Olubukade Akintayo; Aruaye Afeye Obada; Chinelo Ebele Uchendu (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
Maternal health, encompassing the physical and emotional well-being of women during pregnancy, childbirth, and the postpartum period, remains a critical issue in Nigeria, a country facing significant healthcare challenges. Despite being Africa’s most populous nation, Nigeria has one of the highest maternal mortality rates globally, with 512 deaths per 100,000 live births in 2020, representing approximately 14% of global maternal deaths. Key factors contributing to this crisis include complications such as hemorrhage, infections, and eclampsia, alongside a shortage of trained healthcare personnel, particularly in rural areas. Socio-economic disparities further exacerbate the problem. The study discovered that 62.8% of the respondents in this study are unemployed and 42.8% earning less than ₦20,000 per month, restricting their ability to access healthcare. Also, 59.1% of respondents are married, while a significant proportion (32.2%) are aged 20-29 years and 30% are under 20, highlighting trends of early marriage and childbearing. The findings revealed that 44.4% of respondents prefer traditional birth attendants over medical professionals, reflecting a deep-rooted trust in traditional practices. Similarly, accessibility issues are evident, with 61.9% reporting poor infrastructure and long travel distances to healthcare facilities, while 79.4% cite financial barriers. Also, employment instability affects 47.8% of respondents, which further limiting access to care. Widespread dissatisfaction with service quality is reported, with only 18.1% rating healthcare services as excellent. Conclusively, these findings highlight the need for culturally sensitive, community-based interventions that address socio-economic, infrastructural, and cultural barriers to maternal health in Nigeria.